THE EFFECT OF CAPITAL ADEQUACY RATIO, RETURN ON ASSETS, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN AND THIRD PARTY FUNDS OF THE TOTAL VALUE OF LOANS (STUDY IN PRIVATE BANKING LISTED IN INDONESIA STOCK EXCHANGE 2013-2014) - Dwi Iswanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research aims to determine the effect of the Capital Adequacy Ratio (CAR), Return on Assets (ROA), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Third Party Fund (DPK) of the Total Value of Loans in private banking sector companies listed in Indonesia Stock Exchange 2013-2014. The independent variables in this research are CAR (X1), ROA (X2), LDR (X3), NPL (X4) and DPK (X5). While the dependent variable is the Total Value of Loans (Y). This research was conducted by quantitative descriptive methods on the financial statements of private banking sector companies during the period 2013-2014. The total sample is 24 banks. Test equipment used to test the research instrument in the form of classical assumption (normality, multicollinearity, heteroscedasticity, and autocorrelation test). Testing of the hypothesis is done by multiple liniear regression model, the F test, dan t test.The results of this research indicate that the CAR is negative significant, while the LDR and DPK is positive significant. ROA and NPL is not significant. Meanwhile, as the simultaneously CAR, ROA, LDR, NPL, and DPK of the Total Value of Loans is positive significant.Keywords: Total Credit, Capital Adequacy Ratio, Return On Assets, Loan to Deposit Ratio, Non Performing Loan , and Third Party Fund.